Understandings, attitudes, practices and responses to GHB overdose among GHB consumers - Jack Freestone; Nadine Ezard; Adam Bourne; Jonathan Brett; Darren M. Roberts; Mohamed Hammoud; Anthony Nedanoski; Garrett Prestage; Krista J. Siefried (BMC, 2023)
Abstract Background Gamma-hydroxybutyrate (GHB) is used at disproportionately high rates within sexuality and gender diverse communities and carries a high risk of overdose. GHB overdose can result in death. Internationally, recent increases in GHB overdoses have been observed. Coronial reviews of GHB-related death highlight the pivotal roles that bystanders to GHB overdose play in preventing fatality. No research has examined, in detail, how bystanders respond to GHB overdose. This qualitative study was conducted among people who use GHB and explored how they responded upon witnessing a GHB overdose experienced by someone else. Methods Interviews were conducted with 31 sexuality and gender diverse Australian residents reporting three or more occasions of GHB use in the previous 12 months. Participants were asked questions about witnessed GHB overdose, their actions and decision-making processes throughout overdose. Data were analysed thematically. Results Participants described witnessing GHB overdose, commonly in private settings involving sexualized GHB use. Variable definitions of GHB overdose were reported, ranging from GHB-induced symptoms of distress to comatose intoxication. Drastic actions to keep someone alert and responsive post-GHB ingestion were reported; these included the administration of stimulant substances and citrus. Decisions to call or not call for emergency medical services (EMS) were influenced by many circumstantial variables. In most instances, an EMS call was resisted and response practices deviated from established first aid protocols. Conclusions GHB overdose prevention and response training programs targeting people who use GHB are urgently required. These education interventions ought to address inaccuracies that inform street remedies for GHB overdose, teach people how to safely check breathing and response, promote basic first aid principles and address barriers to contacting EMS.